2012
DOI: 10.3758/s13415-012-0092-z
|View full text |Cite
|
Sign up to set email alerts
|

Gut feelings and the reaction to perceived inequity: The interplay between bodily responses, regulation, and perception shapes the rejection of unfair offers on the ultimatum game

Abstract: It has been robustly demonstrated using the ultimatum game (UG) that individuals frequently reject unfair financial offers even if this results in a personal cost. One influential hypothesis for these rejections is that they reflect an emotional reaction to unfairness that overrides purely economic decision processes. In the present study, we examined whether the interplay between bodily responses, bodily regulation, and bodily perception (“interoception”) contributes to emotionally driven rejection behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 50 publications
1
85
0
2
Order By: Relevance
“…Indeed, it was shown that anger mediated the relationship between the magnitude of offers and acceptance rates such that more anger resulted in decreased acceptance rates (Srivastava et al, 2009). Congruently, psycho-physiological findings showed that unfair UG-offers were associated with increased sympathetic arousal as measured by skin conductance response (SCR; van't Wout et al, 2006) and increased emotional orienting response as measured by heart-rate (HR) deceleration (Osumi and Ohira, 2009; though mixed results were shown by Dunn et al, 2012). An example for individual differences in the emotional response to UG-offers was recently shown in a study in which greater resting HR-variability, a marker of trait emotion regulation capability which was measured before playing the UG, predicted subsequent increased acceptance rates (Dunn et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, it was shown that anger mediated the relationship between the magnitude of offers and acceptance rates such that more anger resulted in decreased acceptance rates (Srivastava et al, 2009). Congruently, psycho-physiological findings showed that unfair UG-offers were associated with increased sympathetic arousal as measured by skin conductance response (SCR; van't Wout et al, 2006) and increased emotional orienting response as measured by heart-rate (HR) deceleration (Osumi and Ohira, 2009; though mixed results were shown by Dunn et al, 2012). An example for individual differences in the emotional response to UG-offers was recently shown in a study in which greater resting HR-variability, a marker of trait emotion regulation capability which was measured before playing the UG, predicted subsequent increased acceptance rates (Dunn et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…Congruently, psycho-physiological findings showed that unfair UG-offers were associated with increased sympathetic arousal as measured by skin conductance response (SCR; van't Wout et al, 2006) and increased emotional orienting response as measured by heart-rate (HR) deceleration (Osumi and Ohira, 2009; though mixed results were shown by Dunn et al, 2012). An example for individual differences in the emotional response to UG-offers was recently shown in a study in which greater resting HR-variability, a marker of trait emotion regulation capability which was measured before playing the UG, predicted subsequent increased acceptance rates (Dunn et al, 2012). Further support for the role of emotion regulation in one's response to UG-offers stems from findings such that depleting cognitive control resources resulted in decreased acceptance rates (Halali et al, 2014), while explicitly instructing to regulate emotions resulted in increased acceptance rates (van't Wout et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…outcomes (Ben-Shakhar et al, 2007;Dunn et al, 2012;Joffily et al, 2014;Sanfey et al, 2003;van't Wout et al, 2006). In our setting this possibly indicates that the players view mutual losses as the most alerting events in the course of the game, and that the ANS responses to other events (mutual gains and one-sided losses and gains) remain undetected in our study.…”
Section: Discussionmentioning
confidence: 74%
“…This seemingly irrational choice is thought to be driven by negative emotions, such as anger or frustration, in response to unfair treatment. In this game, individuals with a lower HRV tended to reject unfair offers compared with individuals with a higher HRV (Dunn et al, 2012;Harlé et al, 2010), which suggests that inhibitory control processes promote the rational choice. The resting HRV was also measured in conjunction with another decision-making task, a gambling task in which the participants were asked to decide between a "sure" option and a "gambling" option (Sütterlin, Herbert, Schmitt, Kübler, & Vögele, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…For instance, Harlé, Allen, and Sanfey (2010) and Dunn, Evans, Makarova, White, and Clark (2012) investigated the relation between the resting HRV and the emotional influence on decision making using the ultimatum game, which has two players: a proposer and a responder (Dunn, Evans, Makarova, White, & Clark, 2012;Harlé et al, 2010). The proposer makes an offer for how to divide a sum of money, and if the responder accepts the offer, then the proposal is implemented.…”
Section: Introductionmentioning
confidence: 99%